Exploring The Potential Of Java Mountain Flora Collections As Interpretive Materials For Tourism At The Baturraden Botanical Garden - Fahriza Junizar; Shafira Hanindita (Politeknik Negeri Bandung, 2026)
As an essential ex-situ conservation area, the Baturraden Botanical Garden (BBG) plays a crucial role in preserving Javanese mountain flora, particularly threatened endemic species such as Nepenthes adrianii, Scutellaria slametensis, and Homalomena bellula. However, the integration of these botanical collections into structured destination interpretation ecosystems remains under-optimized. This study aims to evaluate the potential of BBG’s flora collections as primary interpretive materials and design a customized tourism interpretation framework tailored to visitor psychographics. Employing a qualitative descriptive methodology, data were gathered through semi-structured interviews, field observations, and comprehensive literature reviews. The empirical results reveal that while BBG curates 722 plant species systematically arranged across taxonomic and thematic zones, its visitor profile is highly concentrated within the youth demographic (aged 17–27), predominantly comprising students with a strong preference for active educational experiences. Consequently, this study establishes that a direct interpretation mechanism—specifically structured guided walks utilizing interactive, experiential pedagogies—is the most effective strategy. The proposed interpretive content centers on endemic flora taxonomy and core conservation values to actively enhance visitors' pro-environmental behavior. Operational diagnostics reveal that limited human resource capacity and a lack of certified local guides act as critical institutional constraints. Ultimately, these findings underscore that strategic botanical interpretation not only transforms ex-situ collections into actionable conservation education mediums but also strategically reinforces the destination’s competitive identity as a sustainable ecotourism hub.